2018
DOI: 10.1038/s41467-018-04425-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic inhibition of protein phosphatase-2A achieves durable immune-mediated antitumor activity when combined with PD-1 blockade

Abstract: Mounting evidence suggests that inhibition of protein phosphatase-2A (PP2A), a serine/threonine phosphatase, could enhance anticancer immunity. However, drugs targeting PP2A are not currently available. Here, we report that a PP2A inhibitor, LB-100, when combined with anti-PD-1 (aPD-1) blockade can synergistically elicit a durable immune-mediated antitumor response in a murine CT26 colon cancer model. This effect is T-cell dependent, leading to regression of a significant proportion of tumors. Analysis of tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 40 publications
2
60
0
Order By: Relevance
“…Open access the ubiquitin-specific peptidase inhibitor spautin-1, the antibiotic bleomycin, the protein phosphatase-2A inhibitor LB-100, the Chinese herbal medicine component shikonin and capsaicin [34][35][36][37][38] and (8) numerous physical interventions, encompassing various forms of ionizing radiation, extracorporeal photochemotherapy, hypericinbased photodynamic therapy (PDT), near-infrared photoimmunotherapy, high hydrostatic pressure, severe cytotoxic heat shock, nanopulse stimulation and electrohyperthermia. [39][40][41][42][43][44][45][46][47][48][49] Importantly, dose and administration schedules have a major impact on the ability of many of these agents to initiate productive ICD.…”
Section: Introductionmentioning
confidence: 99%
“…Open access the ubiquitin-specific peptidase inhibitor spautin-1, the antibiotic bleomycin, the protein phosphatase-2A inhibitor LB-100, the Chinese herbal medicine component shikonin and capsaicin [34][35][36][37][38] and (8) numerous physical interventions, encompassing various forms of ionizing radiation, extracorporeal photochemotherapy, hypericinbased photodynamic therapy (PDT), near-infrared photoimmunotherapy, high hydrostatic pressure, severe cytotoxic heat shock, nanopulse stimulation and electrohyperthermia. [39][40][41][42][43][44][45][46][47][48][49] Importantly, dose and administration schedules have a major impact on the ability of many of these agents to initiate productive ICD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the PP2A regulatory subunit B55δ was identified in an in vivo shRNA screen whereby loss of B55δ resulted in T cell expansion, increased tumor infiltrating lymphocyte (TILs) and enhanced production of IFN-γ and granzyme [119]. A recent study demonstrated that PP2A inhibition with LB100 enhanced the efficacy of anti-PD-1 treatment, potentially through activation of mTORC1 which resulted in reduced differentiation toward Tregs and increased tumor infiltrating CD8+ T cells [120]. A better understanding of which PP2A-B regulatory subunits contribute to these functions combined with additional studies that utilize PP2A modulating strategies in in vivo immune-competent settings may help to elucidate the seemingly contrasting roles of PP2A in tumor immunity.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Then, DCs acquire high capability to migrate, to phagocytose dying cells, to process more efficiently caspase-cleaved cellular proteins (i.e., NM-neoAgs), and to cross-prime CD8 + T cells that can provide tumor control 35,38,41,42 , on the one hand, and immunopathology in various forms of chronic inflammatory diseases, on the other hand 37,[43][44][45][46][47][48] . In addition, several studies found that ICD synergizes with ICB therapy to further improve T cell responses against different tumors, proposing hence the hypothesis that ICD converts tumor cells into endogenous vaccine and boosts the ICB effects [49][50][51][52][53][54] . However, despite the large body of evidences on how ICD occurs, few evidences have been reported about the nature of antigens becoming immunogenic upon ICD 41,42 .…”
mentioning
confidence: 99%